Analysis on Indonesia's beef import - Ari Rudatin (Universitas Islam Indonesia, 2016)
This research aims to analyze the effect of imported beef price, per capita income (GDP), and domestic beef price toward the volume of Indonesia's beef import within the period of 1998-2014 by using Error Correction Model (ECM) analysis method. The research result shows that the variables used in this research have significant effect in short term, except per capita income. In long term, all of the variables have significant effect toward beef import. The conducted Wald test displays that restriction is invalid wh